Development of a Single-Phase DSP based Power Quality Analyzer using New Signal Processing Algorithms for Detection and Classification - Radil, Tomas (2009)
In this paper, the development of a single-phase digital signal processor (DSP) based power quality analyzer is described. In this stage of development, special attention is devoted to the selection of the signal processing algorithms to be implemented in the prototype. The algorithms must be capable of efficiently detecting and classifying the large range of power quality disturbances that can vary immensely either in amplitude or duration. The broad range of disturbance types is also an important factor since different algorithms may be required for the detection of smaller classes of disturbances.